1997
DOI: 10.1046/j.1469-7580.1997.19040533.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern of the maxillary sinus in the Japanese macaque (Macaca fuscata): reflections on the structural role of the paranasal sinuses

Abstract: To investigate the claim that the primate paranasal sinuses possess not a functional but a structural role associated with the skull architecture (Blaney, 1990), the relationship between the maxillary sinus and the skull architecture was studied ontogenetically in 30 skulls of male and female Japanese macaques (Macaca fuscata). Coronal CT scan series and computerised 3-dimensional images served to evaluate the maxillary sinus. The definitive hemispherical shape of the sinus was already achieved after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 24 publications
7
44
0
Order By: Relevance
“…A review of the available literature suggests, however, that the individual growth of the paranasal sinuses has been almost neglected. While numerous authors have reported ontogenetic data about the human paranasal sinuses [14][15][16][17][18], to our knowledge, very few studies have been done on nonhuman primates [2,19]. The latter studies on skull pneumatization of nonhuman primates, however, are cross-sectional in design and cover only a part of ontogeny.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the available literature suggests, however, that the individual growth of the paranasal sinuses has been almost neglected. While numerous authors have reported ontogenetic data about the human paranasal sinuses [14][15][16][17][18], to our knowledge, very few studies have been done on nonhuman primates [2,19]. The latter studies on skull pneumatization of nonhuman primates, however, are cross-sectional in design and cover only a part of ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…While this relationship is certainly evident for hominoids, factors other than body mass are likely to influence the pneumatization of the alveolar process in macaques. Indeed, whereas M. nemestrina, a monkey with an average body mass of 7.8 kg [35], possesses a sinus that excavates deeply into the alveolar process, the sinus floor of the heavier Japanese macaque (average body mass: 10.5 kg [35]) is well above the tooth roots [2].…”
Section: Morphology Of the Maxillary Sinusmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent cross-sectional study suggested that the difference in MS size between the orangutan and the Japanese macaque results in part from a different growth pattern . While considerable research has been conducted on the postnatal growth of the MS of humans and some nonhuman primates [Schaeffer, 1920;Ariji et al, 1994;Koppe and Nagai, 1997;Koppe et al, in press], our knowledge about the growth pattern of the sinus spaces of nonprimate mammals is rather limited. Apart from a report on the prenatal growth of the MS of the rat [Vidic, 1971], most studies conducted on nonprimate mammals so far dealt with adults [Paulli, 1900a-c;Negus, 1958;Hillmann, 1975;Pohlmeyer, 1977], and only a few researchers have provided quantitative data [Heyne and Schumacher, 1967].…”
Section: Introductionmentioning
confidence: 99%
“…In primates that possess a maxillary sinus, the canine root is placed in the cancellous bone of the maxilla, anterior to the pneumatic space. The root of the canine causes a medial bulge in the inner table of the bone of the maxilla that extends into the nasal cavity 7) . Knowledge of the internal structural configurations may promote a clearer understanding of the development and formation of paranasal pneumatization in primates.…”
Section: Introductionmentioning
confidence: 99%